Effect of Culturally Mediated Right-Favoritism on the Direction of Pseudoneglect on Line Bisection Tasks - Muayqil, Taim A.; Alhaidari, Ghadah M.; Alkuwaiz, Lamia A.; Alotaibi, Nouf A.; Awartani, Hadeel K.; Almufarrej, Alanoud A.; Alqarni, Ghadah S.; Alkeridy, Walid; Alanazy, Mohammed H. (Frontiers in Psychology, 2021)
Objectives Arabs have a right-to-left language and engage in favoring of the right side or limb when implementing daily routine practices. The purpose of this research is to explore the effect this cultural attitude might have on pseudoneglect, by comparing with a southeast Asian sample that has a left-to-right language structure. Methods Participants were from two separate ethnic groups (Arabs and Filipinos), residing in Saudi Arabia, healthy indivudals 18 years and above were allowed to volunteer in the study. The participants were recruited at King Saud University Medical City and the general community by both convenience and snowball sampling. Social demographic information such as gender, age, years of education, dominant hand, was also documented. The line bisection task (LBT) contained 36 randomly assorted lines of 3 different lengths placed at 5 different locations on a white sheet. The percent deviation score (PDS) was used to quantify pseudo-neglect. Tests of statistical significance including t-tests and multivariable regression were performed to determine if differences existed among different demographic variables or among line properties, respectively. Results A total of 256 were enrolled (Arabs 52.3%). The overall PDS mean and standard deviation (SD) was -0.64 (2.87), p = 0.0004, which shows a significant leftward deviation in the entire cohort. PDS was -1.26 (2.68) in Filipinos, and -0.08 (2.94) in Arabs. The difference was statically significant (p < 0.0001). Mixed effects model showed positive changes in the PDS value as the length of the line increased (p <0.0001) and as the line was more rightward placed (p < 0.0001). However, Filipino participants would still exhibit negative changes in the PDS value in comparison to Arabs (p < 0.0001); There were no significant associations between PDS and other factors such as age, years of education and gender. Conclusion Differences found here between two distinct ethnic groups support the hypothesis that certain cultural aspects such as language direction and other cultural practices influence direction and degree of pseudo-neglect.